The Influence of Classroom Arrangement on Increasing Students' Learning Motivation - Primanita Sholihah Rosmana; Sofyan Iskandar; Alifia Nur Azizah HA; Firra Dwi Nur'ani; Nurfenti Widiya Nengsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Implementing class planning is an important factor in increasing student learning motivation at school. This research discusses how good classroom arrangement can positively influence student learning motivation. Through a literature review and case study, this research investigates various effective classroom planning strategies, including furniture arrangement, decoration, lighting, and use of technology in the classroom. The research results show that class planning that takes these factors into account can increase students' interest in learning, concentration and participation in the learning process. The practical implication of this research is the important role of classroom design in creating a learning environment that supports and motivates students.